Measuring Public Innovation in the Nordic Countries: Final Report - Bloch, Carter Walter (CFA Scientific Reports, 2011)
In order to be able to improve our knowledge and understanding of the rate and degree of innovation in the public sector, as well as about its incentives, processes and impact, there is now an increasing awareness of the need for more systematic and comparable data on innovation in the public sector. The objective of the Nordic research project “Measuring innovation in the public sector in the Nordic countries (MEPIN)”’ is to develop a measurement framework for collecting internationally comparable data on innovation in the public sector, which both will contribute to our understanding of what public sector innovation is and how public sector organisations innovate and will develop metrics for use in promoting public sector innovation.